2020
DOI: 10.1111/ijcp.13891
|View full text |Cite
|
Sign up to set email alerts
|

While studies on COVID‐19 vaccine is ongoing, the public’s thoughts and attitudes to the future COVID‐19 vaccine

Abstract: Objective In this study, we aim to investigate the thoughts and attitudes of individuals towards the future COVID‐19 vaccine. Methods This descriptive study was carried out on the web between 10/06/2020 and 10/07/2020. The sample constitutes all individuals above 18 years of age using social media and smartphone. The e‐survey form was shared by the researchers via the web for a month, and those who completed the survey were included in the study and formed the sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
152
2
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(196 citation statements)
references
References 21 publications
26
152
2
7
Order By: Relevance
“…On the contrary, studies among people needed to be vaccinated showed that depressive and anxious symptoms were associated with more acceptability of influenza vaccination ( Chan et al, 2015 ; Lawrence et al, 2020 ; Mohammed et al, 2020 ). It was consistent that one recent survey in Turkey revealed a positive association between anxiety level and the public willingness to get COVID-19 vaccination ( Akarsu et al, 2021 ). Current opinions believed that the widespread psychological distress caused by the pandemic of COVID-19 have impacted health behaviors and vaccination intentions ( Chou and Budenz, 2020 ), however, population-based researches that linked psychological health with COVID-19 vaccination intentions remain scant, especially from the perspective of parents.…”
Section: Introductionsupporting
confidence: 88%
“…On the contrary, studies among people needed to be vaccinated showed that depressive and anxious symptoms were associated with more acceptability of influenza vaccination ( Chan et al, 2015 ; Lawrence et al, 2020 ; Mohammed et al, 2020 ). It was consistent that one recent survey in Turkey revealed a positive association between anxiety level and the public willingness to get COVID-19 vaccination ( Akarsu et al, 2021 ). Current opinions believed that the widespread psychological distress caused by the pandemic of COVID-19 have impacted health behaviors and vaccination intentions ( Chou and Budenz, 2020 ), however, population-based researches that linked psychological health with COVID-19 vaccination intentions remain scant, especially from the perspective of parents.…”
Section: Introductionsupporting
confidence: 88%
“…The manifestation of “fear of the secondary effects” was repeated in this and other studies as the main cause for vaccine hesitation [ 4 , 20 , 39 ]. The high percentage of hesitation in the Spanish population could be partly explained by the rejection of the government’s management in 2020, as indicated by the low confidence in the politicians, the concern when facing a lack of political consensus, and the influence of the political inclination when accepting the vaccine, as shown in our study [ 30 , 40 ].…”
Section: Discussionmentioning
confidence: 61%
“…As for the sources of information, the press and the radio were cited as the most utilized, along with the social networks, which represented a high percentage (25%). These last, more social sources of information could be linked to false news or non-contrasted statements that could derive into an increased hesitancy [ 39 ]. Due to this, scientists from the area of health could be ones who must play the information dissemination role for the population, to transmit the latest findings [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this review, 28 studies depicted the sociodemographic factors associated with public attitudes toward the COVID-19 vaccination. Coherent to findings from the literature [78], the most common factors found to influence vaccine acceptance at the microlevel were age, educational level, gender, race, and income status [23][24][25][26][27][28][29][30][31][32][33][34][35][36][44][45][46][47][48][49][50][51][52][53]63,65,68,[71][72][73]. More willingness to receive a vaccine was reported in the older age group [23,25,27,31,34,35,38,53,65], while resistance, hesitancy, and lack of intention to be vaccinated emerged in the younger age group [29,35,51].…”
Section: Discussionmentioning
confidence: 97%
“…Only one study in the USA reported higher willingness among men [32]. Moreover, other factors were included, such as health condition, people with chronic diseases [29,31,49,65,73], occupation status [27,30,46,50,53,73], marital status [27,28,52], place of residence [29,51,68,73], women being pregnant [29] or having children [30], and those who have health insurance or not [30,31,36,51]. The reviewed articles showed that individuals who had chronic diseases, were employed, married with children, and had health insurance were more likely to report acceptance of COVID-19 vaccines.…”
Section: Sociodemographic Characteristics Shaping Public Attitudes Towards Covid-19 Vaccinesmentioning
confidence: 99%